Historia jako szczególne wyzwanie Kościoła w ujęciu Józefa Nowackiego i Mariana Banaszaka - Rybacki, Rafał (Poznańskie Studia Teologiczne, 2020)
In the presented article history is shown as a special challenge for the Church. The issue raised is presented in relation to historical research and didactic activity of two Polish historians, Józef Nowacki and Marian Banaszak. Two basic questions are asked: what is the specificity of the history of the Church in all theological disciplines? and: What is the basic requirement that this discipline is in the reality of the Church?